Hybrid algorithm for locating mobile station in cellular network - al-Ifan, Belal; Ku-Mahamud, Ku Ruhana (2008)
Locating mobile stations have been attracting an increasing attention from both researchers and industry communities and it is one of the most popular research areas of cellular network.Locating mobile stations using Time of Arrival, Time Difference of Arrival, Angle of Arrival and Received Signal Strength techniques have been widely used.However, more accurate results have been achieved by combining two or more of these techniques.A hybrid algorithm for locating mobile station is proposed by combining Received Signal Strength, Signal Attenuation and Time Difference of Arrival in this paper.